Efektivitas Permainan Pancing Huruf Dan Gambar Terhadap Keterampilan Membaca Pada Anak Di Taman Kanak-Kanak Hang Tuah Padang - Sonia Putri, Alena; Yulsyofriend, Yulsyofriend (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
This research was motivated by the problems encountered in the Hang Tuah Padang Kindergarten, Padang, which showed low reading skills in children due to the inappropriateness of the media in learning to read used by the teacher. This study aims to find out how effective the fishing game with letters and pictures is on children's reading skills at Hang Tuah Padang Kindergarten. The type of research used is a quantitative method with the type of experiment or quashi experimental (pseudo-experiment). The data collection technique in this study is in the form of a test. The population in this study were the children of Hang Tuah Padang Kindergarten. The sampling technique used was purposive sampling technique. Experimental class in class B1 with fishing games for letters and pictures and B2 with letter cards. Data analysis techniques in this study used the Normality Test, Homogenity Test, Hypothesis Test, and Effect Size Test with the help of the SPSS Windows 22 application. The results of the study were obtained based on data analysis that the sig (2-tailed) value was 0.002 <0.05 and the results of the effect test size 1.67 is included in the strong category and shows that there is a significant difference between the reading skills of the experimental class children using letter and picture hooks compared to the control class using letter cards.